MENGHARMONISKAN HUBUNGAN SYIAH DAN SUNNI: PERSPEKTIF USHUL FIKIH (Harmoni, 2014)
The perceived differences between Shiites and Sunnis often causes disharmony in the relationship between the two. The severity of this disharmony is expressed in the form of expiation (takf├«r) and even violence between the two groups. Whereas the difference between a man of grace, if not motivated and caused by the attitudes and actions of fanaticism of school or flow (altaΓÇÿ ashshub), and selfishness or lust (ittib├óΓÇÿ al-haw├ó). To that end, efforts towards the harmonization of these two major schools has become important, and can even be seen as a political and social necessity (dar├╗rah siy├ósiyyah wa-hatmiyyah w├óqiΓÇÿiyyah). One such harmonization effort is done through us├╗l al-fiqh. In this context, the concept of ijtih├ód were revitalized and re-actualized in order to be relevant and important. The application of ijtih├ód as a medium for the harmonization of Shia and Sunni relations must be placed within the framework of the tashw├«b paradigm and not the takhth├« paradigm.
Keywords: Shia; Syiah; harmonization; Ushul Fiqh; harmonisasi; ijtihad